Systematic Literature Review (SLR) Dinamika Perencanaan Pembangunan Infrastruktur Berkelanjutan - Nora Eka Putri; Helmi Helmi; Melinda Noer; Yossyafra Yossyafra (Universitas Teuku Umar, 2021)
This paper contributes to providing an understanding of the dynamics of infrastructure development planning in sustainable development. First, this paper will explain the concept of development from the beginning. The idea is used in a scientific context. Then it will also be described development planning and, in more detail about infrastructure development planning. The research method used is a qualitative approach with systematic literature review (SLR) from various sources of the best journals in googlescholar.com, sciencedirect.com and other relevant sources. The result of this article review is to explain the development of development planning concepts from different periods; development planning context (Developed and Developing countries); categories of physical or social infrastructure development planning; then the sustainability impact of infrastructure development planning, both positive and negative effects of economic, environmental and social aspects, the last about the relationship of development planning with political decision making Based on this paper it is known that the dynamics of infrastructure development planning related to the sustainability of development. Then development planning cannot stand autonomous as an idea or concept that is normative because political decision-making determines the success of the planning. Furthermore, it is necessary to collaborate and synergize development actors in realizing infrastructure development planning. The novelty in this paper is to raise some research questions that can be researched for the future about the dynamics of infrastructure development planning in sustainable development.